Strategic changes in talent development and leadership management in the funeral service industry in Hong Kong - Alan Leung; Yui-yip Lau; Stephanie W. Lee (Public Administration and Policy)
Purpose – This paper identifies the strategic changes and explores the solutions for talent development and leadership management to address the challenges faced by the funeral service industry in Hong Kong. Design/methodology/approach – In this study, semi-structured, in-depth interviews were conducted with seven key personnel (funeral director, salesperson, coffin shop owner, and mortuary transporter) engaged in the funeral service industry in Hong Kong. Thematic coding was used to identify and organize emerging themes from the data. Findings – Four overarching themes were identified: (1) Perception of the funeral service industry in Hong Kong; (2) Recruitment, retention, and talent development; (3) Prospects of the funeral service industry in Hong Kong; and (4) Other novel challenges. The findings reveal continuous, radical, and complex challenges that may exceed the capacity of any leader to develop workable solutions. Originality/value – The funeral service industry is facing radical challenges in modern times. A death-denying attitude is observed, which has severely undermined the study of the funeral service industry.